(untitled) (CIPEEX, 2025)
This paper examines the “listing of assets” (arrolamento de bens) provided for in Article 64 of Law No. 9,532/1997 as an administrative instrument for tax oversight, focusing on its preventive purpose and legal limits. It aims to show that the measure enables the tax administration to monitor the taxpayer’s patrimonial evolution without barring free disposal of assets, while identifying scenarios that may justify more stringent safeguards. Methodologically, it relies on a literature review, statutory analysis, and a survey of Superior Court of Justice precedents, emphasizing the ratio decidendi and practical effects for the Treasury and taxpayers. The findings indicate that asset listing operates as a control and transparency mechanism based on objective fiscal-relevance thresholds and a duty to report material changes, and that it is not equivalent to seizure or unavailability of assets. Attempts to conceal or dissipate assets, however, may trigger autonomous precautionary or constrictive measures under applicable law. It concludes that, by facilitating patrimonial monitoring without restricting asset circulation, the listing regime strengthens legal certainty, discourages fraud, and streamlines tax enforcement while balancing collection efficiency with taxpayer guarantees.